He Whanaungatanga Tīmatanga: The Treaty of Waitangi, Artificial Intelligence and our Schools - Brendon Shaw (New Zealand Journal of Teachers' Work)
This opinion piece explores the intersection of artificial intelligence (AI), The Treaty of Waitangi, and New Zealand schools from the perspective of a Māori educator. The author reflects on personal experiences with AI and discusses the rewards and potential risks Māori face when dealing with artificial intelligence. The piece then looks at how the Treaty’s principles of partnership, participation, and protection can coexist with AI and offers suggestions on how AI can be integrated into Māoritanga in a respectful and collaborative way.